[AR] Tahlil al-Khitab: Min al-Majra al-Lisani ila al-Masra al-Falsafi: Discourse Analysis: From the Linguistic Orbit to the Philosophical Path (Afaq Lughawiyyah, 2024)
This research paper aims to delve into the deep structures of language and thought, to dig into the cognitive roots of discourse, and to travel through historical worlds in order to grasp the path through which discourse analysis has passed. It traces linguistic orbits and philosophical paths that have contributed to its crystallization and formation. Building on this, in the first section, we will attempt to summarize the linguistic research findings on discourse, which emerged in the beginning of the past century with De Saussure, Jacobson, and Benveniste. In the second section, we will move towards elucidating the insights and approaches adopted by the French discourse analysis school with Manguno, Pécheux, and Foucault.